Answer:
x^4-11x^2+28
Step-by-step explanation:
- Set it up
x^2(x^2-4) -7(x^2-4)
2. Multiply
x^4-4x^2-7x^2+28
3. Simplify
x^4-11x^2+28
Step-by-step explanation:
Given,
length of rectangle(l)= 8cm
area of rectangle(A) = 48cm2
breadth of rectangle(b) = ?
Perimeter of rectangle (P)=?
We know ,
Area of rectangle(A) = l×b
or, 48cm2 = 8cm×b
or, 48cm2 = 8bcm
or, 48cm2/8cm = b
or, 6cm = b
or, b = 6cm
therefore, b = 6cm
Perimeter of rectangle (P) = 2(l+b)
= 2(8cm+6cm)
= 2×14cm
= 28cm
therefore, Perimeter of rectangle(P) = 28cm
Now,
According to the question,
Perimeter of rectangle(P) = Perimeter of square(P)
So,
Perimeter of square(P) = 28cm
length of square(l) = ?
Area of square (A) = ?
We know,
Perimeter of square (P) = 4l
or, 28cm = 4l
or, 28cm/4 = l
or, 7cm = l
or, l = 7cm
therefore, l = 7cm
Now,
Area of square (A) = l^2
= (7cm)^2
= 7cm×7cm
= 49cm^2
therefore, area of square (A)= 49cm^2
Divide 15 by 2, then square the amount.
(15/2)^2 = 225/4
Answer:
20%
Step-by-step explanation:
just took test plz mark as brainliest